Psychological Factors as Mediators of Cultural, Social, and Personal Influences on Purchase Decisions among Miniso Consumers in Malang City - Yosanda Zata Aman; Syahva Audia Zulfania Pratiwi; Aditya Budi Krisnanto; Andik Pratama; Diah Widiawati (LPPM Universitas KH A. Wahab Hasbullah, 2026)
The growth of modern lifestyle retail has changed consumer behavior patterns. This study examines the influence of cultural, social, and personal factors on the purchasing decisions of Miniso consumers in Malang City, with psychological factors as a mediating variable. A quantitative explanatory–predictive approach was applied using data from 100 respondents selected through purposive sampling. Data were collected through Likert-scale questionnaires distributed via Google Forms and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that cultural and social factors have positive but insignificant effects on purchasing decisions, while personal factors significantly influence purchasing decisions. Social and personal factors also significantly affect psychological factors, whereas cultural factors do not. In addition, psychological factors significantly influence purchasing decisions and mediate the effects of social and personal factors. These results support the Stimulus–Organism–Response (S-O-R) theory, emphasizing that purchasing decisions are shaped through consumers’ internal psychological processes before resulting in behavioral responses.